Recent progress and perspectives on the relationship between hyperuricemia and periodontitis - Hou, Wenxue; Xia, Xiaomin; Li, Ying; Lv, Hanlin; Liu, Jie; Li, Xue (Frontiers in Immunology, 2022)
Periodontitis is one of the most prevalent diseases in oral cavity, which could not merely lead to the destruction of supporting or surrounding tooth structures but also affect the whole-body health such as the digestive and nervous systems. Epidemiological investigations suggest that in some developed countries, more than 45% or even 50% population are suffering from periodontitis. However, the prevalence increases with age remarkably and it is investigated that a high prevalence (>50%) is affecting the elderly who is over 65 years old. There is an increasing interest in the direct and indirect relationships between periodontitis and hyperuricemia. Currently, hyperuricemia has become the second major metabolic disease in modern society and the prevalence of hyperuricemia among adult males and females is 21.7% and 14.4% respectively. As an inflammatory disease associated with various systemic diseases, periodontitis may have certain connections with hyperuricemia. Partial existing research announces that hyperuricemia could act as an inhibitory factor for periodontitis, while other scholars present that a high uric acid (UA) level is more likely to aggravate inflammatory immune response and leads to more serious tissue destruction. This article provides a detailed and comprehensive overview of the relationship underlying hyperuricemia and periodontitis in the molecular mechanisms. Given the impact of hyperuricemia, this review could provide insight into its comorbidities.